2007
DOI: 10.1007/s11661-007-9237-z
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Curves for Commercial Mg Alloys Determined from Differential Scanning Calorimetry with Improved Heat-Transfer Modeling

Abstract: An improved method is presented for determination of solidification curves, i.e., fraction solid vs temperature, for commercial Mg alloys using heat-transfer model (HTM) differential scanning calorimetry (DSC) curves. A better evaluation of the measured DSC heat flow signal is attained through an independent measurement of the time constant as a function of temperature for the applied equipment. A further improvement is achieved through a more impartial interpretation of the measured DSC curves. Both improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
(92 reference statements)
3
7
0
1
Order By: Relevance
“…Thus, it may be deduced that in contrast to the AZ61 and AZ91 alloys, due to small volume fraction of γ precipitates in AZ31 Mg alloy, no significant signal related to precipitation of γ phase or γ eutectic melting would be detected. A similar behavior was observed in thermal analysis curve of AM50 magnesium alloy 16 . However, solidification process of Mg-Al-Zn system is far from an equilibrium condition even at extremely slow cooling rate of 1 K/min 11 , and coring in α-Mg solid solution occurs and γ phase forms in the microstructure of Mg-Al alloys with down to about 2 wt.…”
Section: Resultssupporting
confidence: 85%
“…Thus, it may be deduced that in contrast to the AZ61 and AZ91 alloys, due to small volume fraction of γ precipitates in AZ31 Mg alloy, no significant signal related to precipitation of γ phase or γ eutectic melting would be detected. A similar behavior was observed in thermal analysis curve of AM50 magnesium alloy 16 . However, solidification process of Mg-Al-Zn system is far from an equilibrium condition even at extremely slow cooling rate of 1 K/min 11 , and coring in α-Mg solid solution occurs and γ phase forms in the microstructure of Mg-Al alloys with down to about 2 wt.…”
Section: Resultssupporting
confidence: 85%
“…One can found that f s(T) increases rapidly from about 0.2 at T ¼ 590 C (863 K) to about 0.5 to 0.6 when vibration starts at lower temperatures of T ¼ 570 C (843 K) and T ¼ 560 C (833 K). The calculated fraction solids are consistent with delicate measurements conducted in a differential scanning calorimeter with a mathematical heattransfer model 23) and thermodynamic prediction by the CALPHAD approach 24) for the AZ91D alloy. Moreover, good agreement can be found between this theoretical calculation and semisolid casting experiment, in which coarsening is assumed to be negligible from the semisolid state to the compete crystallization.…”
Section: Discussionsupporting
confidence: 77%
“…[23,24] Nonferrous tube materials were also considered for application in this study, but were rejected for the reasons given in Section VII-A-1.…”
Section: B Alternative Nonferrous Tube Materialsmentioning
confidence: 99%
“…This temperature is only 42 K higher than the practical liquidus temperature of the alloy, defined by the start of the massive crystallization of the (Mg) phase. [24] After slow cooling in air, the cross section in Figure 3 shows an approximately 30-lm-thick contiguous intermetallic compound layer with a fairly constant aluminum composition of approximately 26 wt pct aluminum and 74 wt pct Fe, or Fe 58 Al 42 (at. pct).…”
Section: A Reaction Between Unprotected Steel Tube and Liquid Alloymentioning
confidence: 99%